PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BATU MULTINDO PERKASA CIGUDEG BOGOR - Sulistiana; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of work motivation and discipline on employee performance at PT Batu Multindo Perkasa Cigudeg Bogor. The research method used is a quantitative method using the classic technique. The data collection technique in this research is by distributing questionnaires to some employees and the data analysis techniques used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis and partial hypothesis test (t) and simultaneous (F). The results of the research show that work motivation and discipline influence employee performance with a regression equation of Y = 0.976 + 0.644 X₁ + 0.000 table or 5,600 > 2,004 then Ho₁ is rejected Ha₁ is accepted. Partially, work discipline influences employee performance with the t-table test results or 0.004 > 2.002, so Ho₂ is rejected and Ha₂ is accepted. The result of simultaneous hypothesis testing is that the calculated F value > F table or 15.685 > 0.000 means Ho₃ is rejected and Ha₃ is accepted. It can be concluded that the research results show that work motivation and discipline influence employee performance at PT Batu Multindo Perkasa Cigudeg Bogor.